EDUKASI STANDAR KUALITAS GULA AREN (Arenga Pinnata Merr) DAN GULA SEMUT ASAL KABUPATEN GARUT UNTUK KUALITAS EKSPOR DENGAN PENDEKATAN SECARA FITOKIMIA: Indonesia - Rustamsyah, Ardi; Asep Darda darul hikam; Anita Kahirunnisa; Farid Permana; Yogi Rahman Nugraha (LP4M STIKes Karsa Husada Garut, 2022)
Palm sugar is one of the processed food products sourced from the processing of sap water from the male flower bunches of the palm tree. Garut Regency is one of the cities for producing palm sugar and ant sugar in Indonesia which is growing rapidly. To improve the quality of palm sugar and ant sugar in Garut Regency, it is necessary to test the palm sugar and ant sugar products according to the characteristics of the quality requirements of the Indonesian National Standardization Agency (BSN), namely SNI 01-3743-199. So that it can compete with palm sugar and ant sugar products from other regions. The purpose of this community service is to maintain the quality and authenticity of palm sugar, by educating craftsmen about palm sugar with Indonesian national standard quality, so that it can be exported. The results of chemical and physical testing of palm sugar, the original product from arrowroot, can meet the quality standards according to SNI 01-3743-199.